Cellulolytic ability of a promising Irpex lacteus (Basidiomycota: Polyporales) strain from the subtropical rainforest of Misiones province, Argentina - Giorgio, Ernesto Martín (2018)
The cellulolytic activity of fungi growing in the subtropical rainforest of Misiones (Argentina) represents a challenge in the technological development of the production of cellulosic bioethanol in the region using native sources. These fungi are promising to obtain sustainable enzyme cocktails using their enzymes. Cellulolytic ability of 22 white-rot fungi isolated from the subtropical rainforest of Misiones-Argentina in agar medium with two types of cellulosic substrates, carboxy-methylcellulose or crystalline cellulose, were comparatively analyzed, and the activity of two cellulolytic enzymes was evaluated in liquid medium. Although all isolates were able to grow and degrade both substrates in agar medium, and to produce total cellulaseFilter paper (FPase) and endo-β-1,4-glucanase (EG) activities in broth, the isolate Irpex sp. LBM 034 showed the greatest enzymatic levels (FPase, 65.45 U L-1; EG, 221.21 U L-1). Therefore, the ITS sequence of this fungus was sequenced and analyzed through a phylogenetic analysis. These results indicate that the isolate LBM 034, corresponding to Irpex lacteus, has a promising cellulolytic ability and enzymes such as EG useful in sustainable saccharification of cellulosic materials in the region.